The added value of SPECT/CT in the evaluation of equivocal skeletal lesions in patients with known malignant disease - Ndlovu, Xolani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Medical Imaging and Clinical Oncology. Nuclear Medicine))--University of Stellenbosch, 2010.